The Impact of Intracoronary Imaging on PCI Outcomes in Cases Utilising Rotational Atherectomy: An Analysis of 8,417 Rotational Atherectomy Cases from the British Cardiovascular Intervention Society Database - Majd B. Protty; Sean Gallagher; Andrew S. P. Sharp; Vasim Farooq; Mohaned Egred; Peter O’Kane; Peter Ludman; Mamas A Mamas; Tim Kinnaird (Journal of Interventional Cardiology)
Introduction. There is increasing evidence supporting the use of intracoronary imaging to optimize the outcomes of percutaneous coronary intervention (PCI). However, there are no studies examining the impact of imaging on PCI outcomes in cases utilising rotational atherectomy (RA-PCI). Our study examines the determinants and outcomes of using intracoronary imaging in RA-PCI cases including 12-month mortality. Methods. Using the British Cardiac Intervention Society database, data were analysed on all RA-PCI procedures in the UK between 2007 and 2014. Descriptive statistics and multivariate logistic regressions were used to examine baseline, procedural, and outcome associations with intravascular imaging. Results. Intracoronary imaging was used in 1,279 out of 8,417 RA-PCI cases (15.2%). Baseline covariates associated with significantly more imaging use were number of stents used, smoking history, previous CABG, pressure wire use, proximal LAD disease, laser use, glycoprotein inhibitor use, cutting balloons, number of restenosis attempted, off-site surgery, and unprotected left main stem (uLMS) PCI. Adjusted rates of in-hospital major adverse cardiac/cerebrovascular events (IH-MACCE), its individual components (death, peri-procedural MI, stroke, and major bleed), or 12-month mortality were not significantly altered by the use of imaging in RA-PCI. However, subgroup analysis demonstrated a signal towards reduction in 12-month mortality in uLMS RA-PCI cases utilising intracoronary imaging (OR 0.67, 95% CI 0.44–1.03). Conclusions. Intracoronary imaging use during RA-PCI is associated with higher risk of baseline and procedural characteristics. There were no differences observed in IH-MACCE or 12-month mortality with intracoronary imaging in RA-PCI.